2013
DOI: 10.21236/ada616641
|View full text |Cite
|
Sign up to set email alerts
|

Development of Composite Scaffolds for Load Bearing Segmental Bone Defects

Abstract: The need for a suitable tissue-engineered scaffold that can be used to heal load-bearing segmental bone defects (SBDs) is both immediate and increasing. During the past 30 years, various ceramic and polymer scaffolds have been investigated for this application. More recently, while composite scaffolds built using a combination of ceramics and polymeric materials are being investigated in a greater number, very few products have progressed from laboratory benchtop studies to preclinical testing in animals. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Cancellous bone lacks mechanical strength due to its high porosity (30–90% porosity) but induces osteogenesis, being frequently used for small defects such as nonunion fractures, maxillofacial and dental defects, and spinal fusion . In what concerns bone grafts, it has been reported that the ideal overall porosity ranges from 60 to 99% . Accordingly, all of the produced scaffolds exhibit the desirable high porosity (>60%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancellous bone lacks mechanical strength due to its high porosity (30–90% porosity) but induces osteogenesis, being frequently used for small defects such as nonunion fractures, maxillofacial and dental defects, and spinal fusion . In what concerns bone grafts, it has been reported that the ideal overall porosity ranges from 60 to 99% . Accordingly, all of the produced scaffolds exhibit the desirable high porosity (>60%).…”
Section: Resultsmentioning
confidence: 99%
“…Taking as reference frequency of 1 Hz, E ′ values, reported as mean ± SD, were 6.75 ± 0.72, 13.3 ± 1.5, and 20.5 ± 2.9 kPa, for n‐HApCS‐untreated, n‐HApCS‐NaOHEtOH, and n‐HApCS‐scCO 2 ‐75/75 samples respectively. Considering that the compression modulus of natural cancellous bone ranges from 50 to 500 MPa, scaffolds exhibiting compression modulus below 25 MPa can be only suitable for non‐load‐bearing applications . The low compression modulus values are attributed to the high porosity of the scaffolds, generally >80%, which is essential for bone ingrowth …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new generation of synthetic bone grafts should combine bioactive and bioresorbable materials. This combination will allow to activate the mechanisms of bone tissue regeneration and accurately reproduce the bone microstructure (Le Nihouannen et al, ; Pilia, Guda, & Appleford, ; Venkatesan & Kim, ). The most popular and widely studied group of biocompatible bone substitutes is bioceramics on the basis of calcium phosphates (CaPs).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this drawback composites containing α‐TCP and substituent characterized by a lower degradation rate can be obtained. Nowadays, hybrid materials composed of a mixture of inorganic, organic or both types of the above components (usually interpenetrate on a scale of less than 1 μm) are the subject of many studies (Das, Zhang, & Noh, ; Pilia et al, ; Zhou et al, ). During the recent studies in the field of bone substitution, the main attention has been focused on two compounds: inorganic HA and biodegradable CTS as an organic component.…”
Section: Introductionmentioning
confidence: 99%